Homeostatic role of B-1 cells in tissue immunity - Suchanek, Ondrej; Clatworthy, Menna R. (Frontiers in Immunology, 2023)
To date, studies of tissue-resident immunity have mainly focused on innate immune cells and T cells, with limited data on B cells. B-1 B cells are a unique subset of B cells with innate-like properties, enriched in murine pleural and peritoneal cavities and distinct from conventional B-2 cells in their ontogeny, phenotype and function. Here we discuss how B-1 cells represent exemplar tissue-resident immune cells, summarizing the evidence for their long-term persistence & self-renewal within tissues, differential transcriptional programming shaped by organ-specific environmental cues, as well as their tissue-homeostatic functions. Finally, we review the emerging data supporting the presence and homeostatic role of B-1 cells across non-lymphoid organs (NLOs) both in mouse and human.